The acceding countries' strategies towards ERM II and the adoption of the euro - an analytical review - Peter Backé; Christian Thimann; Olga Arratibel; Oscar Calvo-Gonzalez; Arnaud Mehl; Carolin Nerlich (European Central Bank (ECB), 2004)
This paper reviews the strategies announced by the ten countries joining the European Union in May 2004 with regard to their intentions for participation in ERM II and the adoption of the euro. The paper examines the economic rationale of the monetary integration strategies declared by most acceding countries with a view to identifying also their potential risks. It does so by making use of several different approaches, including a short review of nominal convergence and a more extensive discussion from an optimum currency area perspective. An important part of the analysis is devoted to the implications of real convergence – i.e. catching-up growth in income and adjustment of the real economic structures towards those prevailing in the euro area – on the patterns of economic dynamics in acceding countries. Other aspects covered are the risks for external competitiveness in the convergence process and the appropriate pace of fiscal consolidation.
Keywords: 330; Europäisches Währungssystem; Euro; EU-Mitgliedschaft; Osteuropa; Malta; Zypern